Determinants of Carbon Emission Disclosure - Gayo Alfani Allam; Vera Diyanty (Journal of Economics, Business, and Accountancy Ventura, 2019)
This research aims to analyze the determinants of carbon emission disclosure. These determinant factors consist of family ownership, financial slack, social reputation, and industry regulation. The study used 537 observations from 179 samples of public companies in natural resource and manufacturing industries in Indonesia for the year 2012- 2014. The result of this research shows that the average level of carbon emission disclosure is only 6, 25%, which indicates that the awareness about carbon emission issues is still low. The regression result shows that financial slack, social reputation, and industry regulation have a significant positive effect on the carbon emission disclosure level, whereas the family ownership has an insignificant effect on the carbon emission disclosure level. This research can be used as a reference by the regulators and companies for creating regulations and policies to reduce and disclose the companies’ carbon emission in order to achieve the national emission target.